2007
DOI: 10.1095/biolreprod.106.059642
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Continuous Treatment with Sildenafil Ameliorates Aging-Related Erectile Dysfunction and the Underlying Corporal Fibrosis in the Rat1

Abstract: Aging-related erectile dysfunction is characterized by a loss of smooth muscle cells (SMCs) and fibrosis in the corpora cavernosa, and functionally by corporal veno-occlusive dysfunction (CVOD). Phosphodiesterase 5 (PDE5A) inhibitors, in part via upregulating inducible nitric oxide synthase (NOS2A), have antifibrotic properties in penile tissues. We aimed to determine whether in the aged rat the chronic long-term treatment with sildenafil ameliorates corporal SMC loss and fibrosis, stimulates NOS2A induction, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
140
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(152 citation statements)
references
References 68 publications
9
140
0
3
Order By: Relevance
“…Chronic PDE5-I administration in cavernous nerve crush injury animal models increased the content of smooth muscle cells and decreased the deposition of collagen in the penile tissue compared with controls. 35,36 Moreover, chronic sildenafil use was associated with a significant reduction in the apoptotic indices and with a greater density of myelinized fibers in rats that underwent cavernous nerve injury. 37 Furthermore, chronic use of PDE5-I contributed to the enhanced expression of nitric oxide synthase in rat corpora cavernosa.…”
Section: Pharmacologic Prophylaxis Of Postoperative Erectile Dysfunctmentioning
confidence: 98%
“…Chronic PDE5-I administration in cavernous nerve crush injury animal models increased the content of smooth muscle cells and decreased the deposition of collagen in the penile tissue compared with controls. 35,36 Moreover, chronic sildenafil use was associated with a significant reduction in the apoptotic indices and with a greater density of myelinized fibers in rats that underwent cavernous nerve injury. 37 Furthermore, chronic use of PDE5-I contributed to the enhanced expression of nitric oxide synthase in rat corpora cavernosa.…”
Section: Pharmacologic Prophylaxis Of Postoperative Erectile Dysfunctmentioning
confidence: 98%
“…36 An antifibrotic effect by vardenafil and sildenafil was observed in the penile tunica albuginea in the rat model of Peyronie's disease, and in the case of sildenafil in the aged corpora smooth muscle. 37,38,12 In order to confirm and expand those findings by studying not only BCNR, but also unilateral cavernosal nerve resection (UCNR), and by using another PDE5 inhibitor, we have determined: (a) how a unilateral nerve injury compares to the more severe BCNR, and (b) whether sildenafil has similar anti-fibrotic properties as vardenafil and works via iNOS induction.…”
Section: Introductionmentioning
confidence: 98%
“…3,10 Several recent studies addressing CVOD in the aged or diabetic rat suggests that this form of erectile dysfunction is associated with the loss of SMC and excessive deposition of collagen fibers within the corpora, and that the long-term continuous administration of PDE5 inhibitors may counteract these processes. [11][12][13] It is likely that this occurs through the maintenance of high levels of cGMP, since this compound reduces collagen synthesis and the activation of the pro-fibrotic TGFb1 pathway and protects SMC from apoptosis, while stimulating the spontaneous induction of inducible nitric oxide synthase (iNOS, also known as NOS2). [14][15][16][17][18][19][20][21][22][23] The expression of iNOS in certain non-immunological tissues is assumed to be a defense mechanism against fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was reported that p42/44 kinase is a downstream effector of the transforming growth factor-beta 1 (TGF-b1) signaling pathway (He et al 2010). TGF-b1 expression is increased in aging trabecular fibroblasts and reported to be the main stimulator of collagen synthesis, inducing cavernosal fibrosis and promoting ED (Ferrini et al 2007;Ryu et al 2004). We hypothesize that increased p42/44 activation in aged ECM component may be a downstream event of the TGF-b1 pathway, adding a new piece in the complex puzzle of aging CC signaling events.…”
Section: Discussionmentioning
confidence: 89%
“…However, and regarding ED, only a study has reported that aged erectile tissue presents low percentage of proliferating cells (Ferrini et al 2007). Nonetheless, CC proliferation with age progression was never evaluated and quantified.…”
Section: Discussionmentioning
confidence: 99%